Active dynamic vibration absorber for broadband control of a multi-mode system: Simulation and experimental verification - Ismail L., ladipo; Abdul Muthalif, Asan Gani (Multi-Science Publishing Company, 2012)
The control of broadband steady state vibration amplitude of a multi-mode system is presented. This objective is achieved using an Active Dynamic Vibration Absorber (ADVA). The stiffness property of the ADVA is adaptively tuned to attenuate the vibration of the multi-mode system at resonance. The ADVA detects the excitation frequency of the multi-mode system and calibrates its stiffness property to give the required stiffness for that mode. To implement the ADVA, a prototype model with low modal frequencies is designed. The equations of the steady state response of the multi-mode system with the attached ADVA are derived. The behavior of the prototype model when the ADVA is attached to different locations is used to determine the optimal location of the ADVA. The simulation result shows a reduction in the broadband of the multi-mode system. The result of the implementation of the ADVA reveals a 46% , 73% and 97% vibration amplitude reduction at first, second and third mode of the multi-mode system respectively.